Interrelationship Between Age, Gender, and Weight Status on Motor Coordination in Italian Children and Early Adolescents Aged 6-13 Years Old - Giuseppe Battaglia; Valerio Giustino; Garden Tabacchi; Massimo Lanza; Federico Schena; Valentina Biino; Matteo Giuriato; Maria Chiara Gallotta; Laura Guidetti; Carlo Baldari; Antonino Gennaro; Antonio Palma; et al. (Frontiers Media S.A., 2021)
Although numerous evidences reported a negative correlation between motor coordination (MC) and overweight/obesity in children and adolescents, the interrelationship between age, gender, and weight status is still debatable. Hence, the aim of this cross-sectional study was to examine the association between MC and weight status according to age and gender across childhood and early adolescence in a large sample of Italian elementary and middle school students. A number of 1961 Italian school students (1,026 boys, 935 girls) was stratified in three consecutive age groups (6-7, 8-10, and 11-13 years) and four weight status categories (underweight, normal weight, overweight, and obese) according to Cole's body mass index (BMI) cut-off points for children. MC performance was assessed measuring motor quotient (MQ) with the Körperkoordinationstest für Kinder (KTK). Results showed significantly lower MQ levels in children in overweight (OW) and with obesity (OB) in both sexes for all age groups than peers in normal weight (NW), except in 6-7-year-old boys. Girls in OW and with OB had similar MQ levels across all age groups, while younger boys in OW and with OB showed higher MQ levels than older ones (p < 0.05). The 6-7-year-old boys showed better MQ levels than girls peers in NW, OW, and with OB, while 8-10-year-old boys in underweight (UW), NW, and OW; and 11-13-year-old boys only in NW (p < 0.05). No interaction effect was found between age, gender, and weight status on MQ levels. These outcomes showed the negative impact of higher weight status on MC performance according to age and gender, pointing out the importance of planning targeted motor programs that consider these variables to improve MC performance.